2015
DOI: 10.1111/crj.12407
|View full text |Cite
|
Sign up to set email alerts
|

Association of multiple genetic variants with chronic obstructive pulmonary disease susceptibility in Hainan region

Abstract: This study is the first to provide evidence of importance of rs9296092 and rs950063 for risk of COPD in Hainan Province. Further studies are needed to characterize the functional sequences that cause COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…rs9296092 is located in intergenic regions that lie in the gene region between the zinc finger and BTB domain containing 9 and BCL2-antagonist/killer1 (ZBTB9-BAK1) at chromosome 6 p21.32. Ding et al also reported that in a case-control study, rs9296092 was associated with the greatest increase in the risk of COPD in the Hainan Province of China [74]. In our current study, we found that the A allele of rs9296092 (OR = 1.832, 95% CI 1.005-3.34, P < 0.045) is also a risk factor for COPD development.…”
Section: The Role Of Six Risk Snps In Copdsupporting
confidence: 71%
“…rs9296092 is located in intergenic regions that lie in the gene region between the zinc finger and BTB domain containing 9 and BCL2-antagonist/killer1 (ZBTB9-BAK1) at chromosome 6 p21.32. Ding et al also reported that in a case-control study, rs9296092 was associated with the greatest increase in the risk of COPD in the Hainan Province of China [74]. In our current study, we found that the A allele of rs9296092 (OR = 1.832, 95% CI 1.005-3.34, P < 0.045) is also a risk factor for COPD development.…”
Section: The Role Of Six Risk Snps In Copdsupporting
confidence: 71%
“…The COPD is more common in people who have a COPD family history 4 . The COPD was also showed a high risk in identical twins than fetal twins 5 , which means genetic factor play a key role in COPD etiology [6][7][8] . Therefore, to identify the genetic factor about smoking and inflammatory in COPD is beneficial to early prevention and accurate diagnosis of COPD.…”
Section: Introductionmentioning
confidence: 96%